Dampak Implementasi Kurikulum MBKM: Analisis Kepuasan dan Persepsi Dosen dan Mahasiswa - I Ketut Suastika; Vivi Suwanti; Rosita Dwi Ferdiani; Wahyudi Harianto (Universitas Mathla'ul Anwar Banten, 2022)
his study aims to describe the impact of the implementation of the MBKM curriculum based on an analysis of the satisfaction and perceptions of lecturers and students. This study uses a mixed method where data is collected with instruments in the form of questionnaires and interviews. Based on the research results, the impact of implementing the MBKM curriculum has a good level of satisfaction for students and lecturers, especially satisfaction with the service system and support from the Faculty. Lecturers' perceptions of the impact of the MBKM curriculum implementation are very beneficial for students. Lecturers prepare students by providing lecture methods that are as close as possible to the case in the world of work.